Analysis and Design of Inventory Management Information Systems at PT. XYZ - Nia Kumaladewi; Ryan Faatih Firdaus (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2025)
This study aims to analyze and design an Inventory Management Information System (IMIS) for PT. XYZ, a company that currently relies on manual inventory processes, leading to inefficiencies and operational delays. To address these challenges, the IMIS was developed using the Rapid Application Development (RAD) methodology, which followed three key stages: requirements planning, design workshop, and implementation. In the requirements planning stage, comprehensive user needs and system specifications were gathered. During the user design phase, iterative prototyping and continuous feedback sessions helped refine the system’s interface and functionalities. The rapid construction phase saw the development of core features—such as real-time inventory tracking, automated restocking alerts, and detailed transaction histories—using PHP, HTML, JavaScript, and MySQL. Finally, in the cutover phase, pilot testing demonstrated that the system reduced material search times from 15–30 minutes to nearly instantaneous retrieval, significantly improving inventory accuracy and overall operational efficiency. Further research is needed to evaluate its long-term performance and scalability. This study not only highlights the practical advantages of the RAD-based approach but also offers a promising model for organizations seeking to modernize their inventory management practices.